Lessons for psychology laboratories from industrial laboratories. (July 2017) - Gomez, Pablo; Anderson, Autumn R; Baciero, Ana
In the past decade there has been a lot of attention to the quality of the evidence in experimental psychology and in other social and medical sciences. Some have described the current climate as a 'crisis of confidence'. We focus on a specific question: how can we increase the quality of the data in psychology and cognitive neuroscience laboratories. Again, the challenges of the field are related to many different issues, but we believe that increasing the quality of the data collection process and the quality of the data per se will be a significant step in the right direction. We suggest that the adoption of quality control systems which parallel the methods used in industrial laboratories might be a way to improve the quality of data. We recommend that administrators incentivize the use of quality systems in academic laboratories.